The Development of Reflective Thinking in the First Six Years of Teaching - KÁLMÁN SÁNTHA (Indonesian Research Journal in Education |IRJE|, 2018)
The aim of this paper is to investigate the development of reflective thinking in the first six years of a beginner teacher’s career. The qualitative study involved a beginner teacher of English in a primary school, who was selected on the basis of availability. Changes in reflective thinking by means of a structured reflective diary after three and six years were studied. In the reflective diary created at the end of the third and sixth years, the teacher had to answer the following questions: What am I doing well? Why? How do I know I have to do so? What do I have problems with? Why? Where do I make mistakes? What chances of development do I have? The processing of the diaries was done using content analysis, combining deductive and inductive logic. The basis of main codes and sub-codes was set up, also relying on triangulation. The reliability of coding was ensured by intra-coding. The results showed that after the third year, reflections appeared at a technical level, usually answering the question “what?”. After the sixth year, the reflections were more complex, and often dealt with insights about teachers’ activity. Besides “what?” questions “why?” and “how?” were in focus. The results have shown that during continuous reflection teachers may develop and improve a system combining theoretical and practical skills that can embrace the entirety of pedagogical work. The results show that continuous reflection contributes to the differentiation of pedagogical knowledge. The paper addresses those who are interested in the exploration, analysis, and development of reflective thinking.